Development of P-resonant controller for Z-source three phase inverter - Mehda, Ayoub (2015)
This project presents a P-Resonant (PR) controller to control the output current and voltage for a Z-Source three phase inverter. The model scheme is developed and simulated in MATLAB/Simulink software environment. The Z-Source inverter is special type of inverter that provide the voltage boost capability in which it results with an output voltage greater than the input DC voltage and that cannot be obtained using the traditional inverter. Using the P-Resonant controller, the inverter reference tracking performance can be enhanced. Simulation study of P-Resonant controller is presented. The results show the P-Resonant controller achieves very good results with a good tracking capability for the reference values of both current and voltage. Besides, it maintains a small error signal which makes it a preference controller compared to the other traditional controllers.